Development of a Captiva EMR-lipid clean-up and LC-MS/MS methodology for detecting H2 receptor antagonists in functional foods and food-medicine homology materials - Guodong Shan; Xiuqin Fan; Qingcheng Wang; Li Zhang; Lijun Ge; Weibo Lu; Jing Xue; Kang Chen; Zejun Wang; Qing Shen (Applied Food Research)
The inappropriate use of H2 receptor antagonists (H2RAs) in functional foods (FFs) and food-medicine homology materials (FMHs) designed to enhance gastrointestinal function (IGF) presents health risks due to potential adverse effects. In this study, an analytical method that integrates Captiva EMR-Lipid (CEL) solid-phase extraction (SPE) with liquid chromatography tandem mass spectrometry (LC-MS/MS) has been developed for the detection of H2RAs (nizatidine, famotidine, cimetidine, ranitidine, and lafutidine) in these products. Through the optimization of CEL-SPE parameters, such as using 200 mg of sorbent and eluting with ACN/water (80/20, v/v), the recovery rates of H2RAs in IGF-FF and IGF-FMH ranged from 87.4 % to 94.6 % and 90.2 % to 97.1 %, respectively. The assessment of matrix effects revealed that the five H2RAs exhibit matrix suppression, necessitating the construction of matrix-matched standard curves with correlation coefficients (r2) exceeding 0.9991. The detection limits ranged from 0.4 to 0.8 μg·kg−1 and the quantification limits ranged from 1.3 to 2.7 μg·kg−1, with recovery rates spanning from 85.4 % to 97.1 % and relative standard deviations ≤ 15 %. The successful development of this technique not only helps safeguard consumer health but also provides scientific basis and technical support for market supervision, thereby preventing and addressing food safety risks.